1996
DOI: 10.1111/j.1442-2042.1996.tb00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Oxalate Content of Foods by the Oxalate Degrading Bacterium, Eubacterium Lentum WYH‐1

Abstract: Eubacterium lentum WYH-1 was able to efficiently decompose the oxalate in foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The oxalate-degrading human bacteria described to date were only anaerobes including Oxalobacter formigenes, Eubacterium lentum, Bifidobacterium adolescentis, and Propionibacterium acnes (2,17,19). There has been no previous report of facultatively anaerobic oxalate-degrading E. faecalis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The oxalate-degrading human bacteria described to date were only anaerobes including Oxalobacter formigenes, Eubacterium lentum, Bifidobacterium adolescentis, and Propionibacterium acnes (2,17,19). There has been no previous report of facultatively anaerobic oxalate-degrading E. faecalis.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, oxalate-degrading bacteria has only been studied by a few investigators. In 1994, Ito and associates found another oxalate-degrading organism, Eubacterium lentum, and they purified two enzymes (oxalyl-CoA decarboxylase and formylCoA transferase) that are involved in oxalate degradation (17,19).…”
mentioning
confidence: 99%
“…Other oxalate-degrading bacteria isolated from the human GIT include Eubacterium lentum (22) and Enterococcus faecalis (20 . They observed a reduction in the excreted oxalate in the patients and showed that L. acidophilus and S. thermophilus could reduce oxalate concentrations in vitro, even when their growth was partially inhibited by this compound.…”
Section: Discussionmentioning
confidence: 99%
“…In a related study (230) As an alternative to treatment of patients with these conditions, it is possible to reduce the oxalate content of food prior to its being eaten (176; R. Yoshida, T. Tanaka, and Y. Hotta, 5 March 1994, European patent application 0639329 A1). In one such method, it was shown (132) that the oxalate-degrading bacterium Eubacterium lentum WYH-1, isolated from human feces (133), could completely degrade 1 mg of oxalate per ml in artificial intestinal juice or the oxalate in an infusion of black tea-one of the major sources of oxalate in the human diet (321). Similarly, barley roots in a stirred-tank reactor have been used to reduce the level of oxalate in ginger juice (313).…”
Section: Medical Diagnosis and Treatmentmentioning
confidence: 99%